Analysis of Character Education Values in Visual Arts Learning at SDN 16 Sindue - Sindi Olivia; Andi Imrah Dewi; Kadek Hariana; Rizal Rizal; Andi Rahmaeni (ITScience (Information Technology and Science), 2026)
This study aims to determine the application of character education values in Fine Arts learning for fifth-grade students of SDN 16 Sindue. This study used a descriptive qualitative approach. The research subjects consisted of Fine Arts teachers and fifth-grade students of SDN 16 Sindue. Data collection techniques were conducted through observation, interviews, and documentation. Data analysis techniques used the stages of data reduction, data presentation, and conclusion drawing. Data validity was tested using source triangulation and technical triangulation. Character education values have been integrated into the planning, implementation, and evaluation stages of Fine Arts learning. The most prominent values observed were discipline, independence, and creativity. Discipline appeared in students’ punctuality, preparedness, adherence to rules, and timely assignment completion. Independence was shown through students’ ability to work individually, solve problems on their own, and take responsibility for their work. Creativity emerged in students’ idea generation, imagination development, and production of unique artworks. Teachers played a key role as facilitators, guides, and role models in instilling these values. Based on the research results, it can be concluded that Fine Arts learning can be an effective means of instilling character values in elementary school students. Through creative activities, students not only develop aesthetic abilities but also develop discipline, independence, and creativity in their daily lives.